The Preparation of Mentors Who Support Novice Teacher Researchers - Ann Schulte (Networks: An Online Journal for Teacher Research, 2014)
In my eleven years as a teacher educator at CSU Chico, I have always used action research and self-study to learn about my own practice. I have also taught both credential and MA students the process of AR, but I had yet to lead a cohort of students in a yearlong study. I was excited about the action research requirement of the newly created Rural Teacher Residency (RTR) program. In this program, teacher candidates (called Residents) earned a teaching credential and a Masters degree in 18 months. As part of the RTR program faculty, I had been given the major responsibility of planning and involving the Mentors (i.e. cooperating teachers) in the Residents’ action research process. Therefore, I set out to conduct my own action research to assess the impact of the preparation that I was providing Mentors. I was looking to collect data that would help me to know the success of what had been provided the first year so I could appropriately modify these practices for the following year. My question was: What is the impact of the resources I provide on the ways Mentors perceive their role in this action research process? This paper details the findings from data collected during the first year’s cohort and halfway through the second year’s cohort.